Vaccination against δ-retroviruses : the bovine leukemia virus paradigm - Gutierrez, Gerónimo; Rodriguez, Sabrina M.; de Brogniez, Alix; Gillet, Nicolas A.; Golime, Ramarao; Burny, Arsene; Jaworski, Juan Pablo; Alvarez, Irene; Vagnoni, Lucas Emilio; Trono, Karina Gabriela; Willems, Luc (2018)
Bovine leukemia virus (BLV) and human T-lymphotropic virus type 1 (HTLV-1) are closely related d-retroviruses that induce hematological diseases. HTLV-1 infects about 15 million people worldwide, mainly in subtropical areas. HTLV-1 induces a wide spectrum of diseases (e.g., HTLV-associated myelopathy/tropical spastic paraparesis) and leukemia/lymphoma (adult T-cell leukemia). Bovine leukemia virus is a major pathogen of cattle, causing important economic losses due to a reduction in production, export limitations and lymphoma-associated death. In the absence of satisfactory treatment for these diseases and besides the prevention of transmission, the best option to reduce the prevalence of d-retroviruses is vaccination. Here, we provide an overview of the different vaccination strategies in the BLV model and outline key parameters required for vaccine efficacy.